2015
DOI: 10.1103/physrevb.92.100506
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous transport phenomena inpx+ipysuperconductors

Abstract: Spontaneous breaking of time-reversal symmetry in superconductors with the px + ipy symmetry of the order parameter allows for a class of effects which are analogous to the anomalous Hall effect in ferromagnets. These effects exist below the critical temperature, T < Tc. We develop a kinetic theory of such effects. In particular, we consider anomalous Hall thermal conductivity, the polar Kerr effect, the anomalous Hall effect, and the anomalous photo-and acousto-galvanic effects.Introduction: One of the leadin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
86
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(88 citation statements)
references
References 25 publications
2
86
0
Order By: Relevance
“…In early studies, it was already identified that for certain values of the magnetic flux, the model belongs to the symmetry class AIII and there are chiral symmetry protected edge modes at the boundaries of the ladder [67]. In later investigations, various modified versions of the CL are proposed [69][70][71][72][73][74][75][76][77][78][79], and also realized experimentally in atom-optical setups like photonic lattices [80,81] and cold atoms [82,83]. Intriguing topological features of the CL are reflected in the formation of AB cages [81] and the quantized Thouless pumping [84].…”
Section: The Modelmentioning
confidence: 99%
“…In early studies, it was already identified that for certain values of the magnetic flux, the model belongs to the symmetry class AIII and there are chiral symmetry protected edge modes at the boundaries of the ladder [67]. In later investigations, various modified versions of the CL are proposed [69][70][71][72][73][74][75][76][77][78][79], and also realized experimentally in atom-optical setups like photonic lattices [80,81] and cold atoms [82,83]. Intriguing topological features of the CL are reflected in the formation of AB cages [81] and the quantized Thouless pumping [84].…”
Section: The Modelmentioning
confidence: 99%
“…[27] Therefore, the observed finite Kerr effect was considered within clean multiband models [28][29][30][31][32] and single band models with impurities. [26,33,34] Notwithstanding the significant theoretical interested, to the best of our knowledge the effect of diffractive skew scattering from quantum impurity complexes has been disregarded in the literature, so far. It will therefore be the subject of the present paper.…”
mentioning
confidence: 99%
“…However, each of these two extrinsic mechanisms implies different dependence on impurity concentration as n imp and n 2 imp respectively. The most recent full T -matrix analysis [34] uncovered that skew scattering of low-energy quasiparticle on strong impurities results in anomalous Hall response being linearly proportional to τ ∝ n −1 imp and falling off linearly with inverse frequency. The kinetic approach of Ref.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Also, one-dimensional (1D) systems, for instance, Su-Schrieffer-Heeger (SSH) chain [11] in the presence of sublattice and/or spin degrees of freedom are capable of exhibiting nontrivial phases providing topological insulators [12][13][14][15][16][17][18]. In this framework, several theoretical works have been dedicated to investigating effects of spin-orbit coupling [19], Zeeman magnetic field [20,21], and curvature [22] on topological properties of 1D superlattices by characterizing phase transition points [23]. In addition, a new type of artificial quantum matter lattice composed of multilayer heterostructures of topological insulators and ordinary insulators has been fabricated experimentally which is condensed matter realization of SSH model [24].…”
Section: Introductionmentioning
confidence: 99%